EFEKTIVITAS AGROSCHOOLING DALAM MENINGKATKAN KEMAMPUAN LITERASI SAINS PADA ANAK USIA DINI - Khoirunisa, Faricha Ladhzina; Mukminin, Amirul (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Science literacy is one example of a form of literacy that is important to introduce to children from an early age because at this time they are full of enthusiasm and curiosity about new things. However, currently, science literacy learning at Mutiara An-Naafi’u Kindergarten has not been implemented optimally. In the classroom, learning is still dominated by the use of LKA and the lecture method so that children do not get direct experience which causes children’s science literacy skills not to develop properly. In this study, agroschooling was utilized as a means of science literacy skills in early childhood at Mutiara An-Naafi’u Kindergarten. This study is intended to determine and assess the effectiveness of agroschooling in improving early childhood science literacy skills. This study used a type of quantitative research with an experimental approach using a pre-experimental one-group pretest-posttest design. The subjects involved in the study were kindergarten B group students totaling 27 students. Data were extracted using observation, interview, and test techniques. In addition, data analysis techniques with normality test, T-test, and N-Gain test were also applied with the help of IBM SPSS Statistic 27. Based on the results of the paired sample t-test test, a significance value of 0.00 <0.05 was obtained, indicating a significant difference between the pretest and posttest scores. So it can be concluded that agroschooling is effective in improving literacy skills.